Prophecy of the sisters - Zink, Michelle (New York : Little, Brown, 2009)
In late nineteenth-century New York state, wealthy sixteen -year-old twin sisters Lia and Alice Milthorpe find that they are on opposite sides of an ancient prophecy that has destroyed their parents and seeks to do even more harm.
Keywords: Supernatural -- Juvenile fiction; Good and evil -- Juvenile fiction; Twins -- Juvenile fiction; Sisters -- Juvenile fiction